Analisis Jenis-Jenis Kinayah dalam Surah Yusuf (Pusat Riset dan Inovasi Nasional, 2024)
This study is motivated by the status of Surah Yusuf as ahsanul qashash, which has special characteristics in terms of balagah, particularly the use of kinayah to convey sensitive narratives in a polite manner. This study aims to identify the classification of types of kinayah and reveal the pragmatic functions behind their use in the text. The research method used is descriptive qualitative with heuristic-semiotic analysis techniques, where the primary data is sourced directly from the verses of the Qur'an. Surah Yusuf predominantly uses kinayah 'an al-maushuf to refer to certain entities or positions in order to maintain the dignity of the narrative, in addition to the use of kinayah shifah and nisbah to describe the emotional turmoil of the characters. Functionally, this style of language plays the role of ihtiraz (preventive), mubalaghah (emphasis of meaning), and ta'dzim (respect). The implications of this study confirm that the use of kinayah is not merely linguistic aesthetics, but a medium of moral education that promotes polite interpersonal communication and is relevant to contemporary Islamic ethics.